Application of Internet of Things (IoT) in Monitoring and Controlling Engineering Equipment - Amina Intes; Embrechts Xavier; Ling Barra (Journal of Moeslim Research Technik, 2024)
Research Background: The development of Internet of Things (IoT) technology has presented new opportunities in the field of monitoring and controlling engineering equipment. The use of IoT in this context enables real-time data collection and automatic control of equipment via internet networks, bringing the potential to improve the efficiency and performance of engineering systems. Research Objectives: This research aims to explore the application of Internet of Things technology in the monitoring and control of engineering equipment, and to evaluate its benefits in the context of operational efficiency and cost reduction. Research Methods: The research methods used include literature review, system requirements analysis, IoT infrastructure design, prototype implementation, and functionality testing. The collected data were analyzed to evaluate the performance of the system and the benefits obtained. Research Results: The implementation of IoT in the monitoring and control of engineering equipment successfully shows an increase in operational efficiency and cost reduction. The developed system is able to collect data in real-time, provide accurate and timely information, and enable automatic or remote control of equipment via the internet. Research Conclusion: The application of the Internet of Things in monitoring and controlling engineering equipment promises significant advances in operational efficiency and resource management. By leveraging this technology, organizations can increase productivity, reduce operational costs, and improve overall system reliability.